High Gain Transformer-Less Double-Duty-Triple-Mode DC/DC Converter for DC Microgrid - Mahajan Sagar Bhaskar (16855398) (2019)
High-gain DC/DC converters with high efficiency are needed in dc microgrid owed to the low voltage of power sources, e.g., photovoltaic-cell and fuel-cell. This paper proposed a new high-gain double-duty-triple-mode (DDTM) converter for dc-microgrid applications. The proposed DDTM converter operates in three modes to achieve higher voltage gain without utilizing transformer, coupled inductor, voltage multiplier, and multiple voltage lifting techniques, e.g., triple, quadruple voltage lift. The modes of operation of the converter are controlled through three switches with two distinct duty ratios (double duty) to achieve wide range duty ratio. The operating principle, voltage gain analysis, and efficiency analysis of the proposed converter are discussed in detail and to show its benefits comparison is provided with the existing high-gain converters. The boundary operating condition for continuous conduction mode (CCM) and discontinuous conduction mode (DCM) is presented. The prototype of the proposed converters with 500-W power is implemented in the laboratory and experimentally investigated, which validate the performance and feasibility of the proposed converter. Due to double duty control, the proposed converter can be controlled in different ways and the thorough discussion on controlling of the converter is provided as a future scope. Other Information Published in: IEEE Access License: https://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.1109/access.2019.2902440